A look on mathematical fundamentals for minimax theorem and Nash equilibrium existence - Ferreira, M. A. M. (2020)
We present two results of Game Theory, very important in Economics: minimax theorem and Nash equilibrium existence, together with their mathematical fundamentals. For minimax theorem, the mathematical structure considered is real Hilbert spaces. Moreover, the convex sets strict separation plays here an important role. For Nash equilibrium existence, Kakutani's theorem is the key result to consider. Then follows a presentation of some propositions that identify matches between those outcomes.